Answer:
11/12
Step-by-step explanation:
Calculate the sum
rewrite the fraction
simplify the fraction
Solution 11/12
Answer:
m = 8
Step-by-step explanation:
-2(5 + 6m) + 16 = -90
Start by distributing -2 inside the parentheses. This means you will multiply everything inside the parentheses (5 + 6m) by -2.
-10 - 12m + 16 = -90
Simplify the left side of the equation by combining like terms.
6 - 12m = -90
Subtract 6 from both sides of the equation to isolate the term containing the variable m and to move all other terms to the other side (right) of the equation.
-12m = -96
Divide both sides of the equation by -12 to isolate and solve for m.
m = 8
A. 1/6
b. 6/3
c. 1
I think those are the answers